Investigation on parametric representation of proportional and nonproportional multiaxial fatigue responses - J. Albinmousa (Fracture and Structural Integrity)
This study aims to investigate fatigue damage resulting from multiaxial fatigue, proportional and/or nonproportional, loading by analyzing stresses and strains over a full domain around a representative stress-strain element. Plain stress-strain transformation of multiaxial hysteresis was performed by varying orientation of plane for 0?fi?2?. Parametric representations for both normal and shear stresses and strains were obtained by plotting them in polar figures. These figures show that depending on the applied loading stresses and strains represent definitive known parametric curves. Parametric representation of fatigue damage parameter such as Fatemi-Socie suggests that fatigue damage shall be calculated as the sum of the damage values on all planes. The proposed technique has been shown to improve fatigue life prediction compared to that obtained from the critical plane method.